Analysis of Spread Spectrum Time Domain Reflectometry for Cable Fault Detection - Sharma, Reema; Barge, Piyush; Prasad, Hemant (International Journal of Computer Sciences and Engineering, 2025)
Cable fault detection is crucial and helps to avoid severe damage and maintain continuous functioning of an electrical system. Spread Spectrum Time Domain Reflectometry is considered to be an effective method to detect intermittent faults such as open circuits and short circuits. This paper shows the working and advantages of Spread Spectrum Time Domain Reflectometry (SSTDR). It also includes experimental data analysis performed on low voltage cable using ARC CHASER SSTDR kit manufactured by LIVE WIRE INNOVATIONS.